A phase II study evaluating safety and efficacy of niraparib in patients with previously treated homologous recombination defective metastatic esophageal/gastroesophageal junction/proximal gastric adenocarcinoma - Khalid, Ahmed Bilal; Fountzilas, Christos; Burney, Heather N.; Mamdani, Hirva; Schneider, Bryan P.; Fausel, Christopher; Perkins, Susan M.; Jalal, Shadia (Frontiers in Oncology, 2024)
IntroductionEsophageal adenocarcinoma (EAC) remains a devastating disease and second line treatment options in the metastatic space are limited. Homologous recombination (HR) defects have been described in EAC in up to 40% of patients. Poly (ADP-ribose) polymerase (PARP)1 and PARP2 inhibitors have shown efficacy in HR defective prostate and ovarian cancers. Here, we describe the activity of the PARP inhibitor niraparib in metastatic EAC with HR defects.MethodsIn this single arm Simon two-stage Phase II study, we assessed the safety and efficacy of niraparib in patients with metastatic EAC previously treated with platinum containing chemotherapy harboring defective HR. Defective HR was defined as deleterious alterations in the following HR genes: BRCA1/2, PALB2, ATM, BARD1, BRIP1, CDK12, CHEK2, FANCA, RAD51, RAD51B, RAD51C, RAD51D, RAD54L, NBN, ARID1A and GEN1.Results14 patients were enrolled in this study. The trial was stopped early due to slow accrual. 3 patients did not have post-treatment scans because of rapid clinical decline. The overall response rate (ORR) (95% exact CI) was 0/11 = 0% (0%, 28.49%). The disease control rate (DCR) (95% exact CI) was 2/11 = 18.2% (2.3%, 51.8%). The median PFS was 1.8 months (95% CI = 1.0-3.7). The median OS for evaluable patients was 6.6 months (95% CI =2.7-11.4) and 5.7 months for all patients (95% CI =2.7-10.1). The most common adverse events seen were anemia, fatigue, and thrombocytopenia.ConclusionIn patients with metastatic EAC, single agent niraparib as second line therapy is not an effective option.